Directed technical change and economic growth effects of environmental policy - Kruse-Andersen, Peter K. (Copenhagen, 2016)
"A Schumpeterian growth model is developed to investigate how environmental policy affects economic growth when environmental policy also affects the direction of technical change. In contrast to previous models, production and pollution abatement technologies are embodied in separate intermediate good types. A set of stylized facts related to pollution emission, environmental policy, and pollution abatement expenditures is presented, and it is shown that the developed model is consistent with these stylized facts. It is shown analytically that a tightening of the environmental policy unambiguously directs research efforts toward pollution abatement technologies and away from production technologies. This directed technical change reduces economic growth and pollution emission growth. Simulation results indicate that even large environmental policy reforms have small economic growth effects. However, these economic growth effects have relatively large welfare effects which suggest that static models and exogenus growth models leave out an important welfare effect of environmental policy."